Pendidikan Akhlak di Perguruan Tinggi Islam sebagai Bekal di Dunia Kerja - Zulkarnain, Lutfi; Hafidhuddin, Didin; Handrianto, Budi (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
A series of cases of moral degradation of the nation's children shows that the urgency of moral education in this day and age cannot be avoided. Strengthening good morals in students will encourage these students to grow with the capacity and commitment to do good things and will do everything right. The purpose of writing this article is to provide an overview of the moral values that need to be internalized to Islamic accounting students as their provisions later in the world of work. The method used in writing this article is a literature method with a descriptive analysis approach. The results of the study show that the moral values that need to be internalized to Islamic accounting students as their provisions later in the world of work, include the value of religiosity, the value of hard work, the value of responsibility, the value of honesty, the value of trust, and the value of gratitude. If these values are internalized to Islamic accounting students, it is hoped that in the future when he becomes a sharia accountant who upholds the Islamic accountant code of ethics and avoids corruption.